Carbographite Buckypaper: A Flexible Oxygenated Carbographite Nanofilamentous Buckypaper as an Amphiphilic Membrane (Adv. Mater. Interfaces 8/2018). Issue 8 (23rd April 2018) - Homaeigohar, Shahin; Strunskus, Thomas; Strobel, Julian; Kienle, Lorenz; Elbahri, Mady
Abstract : Despite promising non‐polar adsorptivity, superhydrophobic graphite nanomaterials challenge the dynamic filtration processes due to a fouling effect. In article number1800001, Mady Elbahri and co‐workers introduce amphiphilic carbographite nanofilaments composed of oxidized amorphous carbon and graphite as the structural elements of a buckypaper membrane. The buckypaper membrane separates both polar and non‐polar water pollutants while maintaining a high water permeability, thus holding great promise for industrial application.